Active stiffening of F-actin network dominated by structural transition of actin filaments into bundles. (1st May 2017) - Lin, Shengmao; Han, Xinwei; Tsui, Gary C.P.; Hui, David; Gu, Linxia
Abstract: Molecular motor regulated active contractile force is key for cells sensing and responding to their mechanical environment, which leads to characteristic structures and functions of cells. The F-actin network demonstrates a two-order of magnitude increase in its modulus due to contractility; however, the mechanism for this active stiffening remains unclear. Two widely acknowledged hypotheses are that active stiffening of F-actin network is caused by (1) the nonlinear force-extension behavior of cross-linkers, and (2) the loading mode being switched from bending to stretching dominated regime. Direct evidence supporting either theory is lacking. Here we examined these hypotheses and showed that a reorganization of F-actin network from cross-linked filament state to bundled stress fiber state plays a key role on active stiffening of actin network. We demonstrated through computational models that the stretching of cross-linkers and molecular motors has less impact on the active stiffening, while it is more sensitive to cytoskeleton reorganization during the elasticity sensing. The proposed new mechanism involving the cytoskeletal remodeling was able to integrate discrete experimental observations and has the potential to advance our understanding of active sensing and responding of cells.